Rancang Bangun Keamanan Port Secure Shell (SSH) Menggunakan Metode Port Knockking - Desmira Desmira; Romi Wiryadinata (LPPM Universitas Bina Sarana Informatika, 2022)
Banten Tour Mandiri is a tour and travel service provider, the need for internet use in companies is very much needed so that services in the service sector can be carried out comfortably and effectively. This study aims 1. To design a remote system using port knocking to monitor and supervise internet network access at PT. Banten Tour Mandiri. 2. Overseeing the internet network at PT. Banten Tour Mandiri. 3. Make it easier for companies to manage, supervise when using the existing internet network in the corporate environment. To develop the stability of the existing internet network, but there are several things that have not been considered and implemented, namely security and supervision of the internet network, it is necessary to have a network security system that simplifies security and supervision, by performing the Secure Shell (SSH) Port Security Design Port Knocking Method At PT. Banten Tour Mandiri. The results of this study show that the administrator has successfully performed remote access to the internet network server using the SSH port. Monitoring and management of internet network security can be done using a different PC located in the PT. Banten Tour Mandiri